JUNIOR HIGH SCHOOL STUDENTS' PERCEPTIONS OF PROBLEM BASED LEARNING MODEL IN SCIENCE LEARNING - Febriani, Febby; Azki, Muhammad; Oktavia, Rani (Pendidikan IPA, FMIPA, UNP, 2024)
Problem Based Learning (PBL) is a learning approach that is often used in education in recent years. The purpose of this article is to find out how junior high school students perceive PBL model in science class and the benefits of PBL model in science learning. To find data related to junior high school students' perceptions of problem-based learning models in science classes, the researcher conducted a systematic review of several relevant sources with a period from 2014 to 2023, following the principles of Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). Based on the research results, it is known that the problem solving ability of students who learn using the PBL model is better than students who learn with conventional models. The results of this study prove PBL as an effective learning method for science compared to conventional teaching methods. PBL method is perceived to improve students' knowledge and communication skills. Based on several research results that have been conducted, it can be concluded that the PBL model has a positive impact on learning.